Biochemical constituent, enzyme inhibitory activity, and molecular docking analysis of an endemic plant species,Thymus migricus - Aras, Abdulmelik; Turkan, Fikret; Yildiko, Umit; Atalar, Mehmet Nuri; Kilic, Omer; Alma, Mehmet Hakki; Bursal, Ercan (Springer International Publishing Ag, 2021)
Medicinal plants have been used traditionally since ancient times as alternative medications to treat various human diseases.In this work, we examined the chemical constituent, antioxidant activity, and enzyme inhibition of an endemic plantThymus migricus. The plant extracts showed remarkable inhibition effects against the acetylcholinesterase (AChE), butyrylcholinesterase (BChE), glutathione S-transferase (GST), and alpha-glycosidase (alpha-Gly) enzymes that are linked with some metabolic disorders. IC(50)values (concentration of a sample to inhibit 50% of enzyme activity) for AChE, BChE, GST, and alpha-Gly were found as 18.23 mg/mL, 17.77 mg/mL, 31.5 mg/ml, and 16.5 mg/mL, respectively. Antioxidant activities of water extract ofT. migricus(WET) and methanol extract ofT. migricus(MET) were determined using four in vitro techniques. The extracts showed considerable antioxidant actions on all four techniques. In addition, quinic acid (18.30 mg/g), chlorogenic acid (0.94 mg/g), cynaroside (0.49 mg/g), luteolin (0.21 mg/g), andp-coumaric acid (0.19 mg/g) were characterized as major phenolic compounds using advanced LC-MS/MS technique. The interactions of some phenolic compounds with the enzymes have been investigated using molecular docking studies. The docking analysis results revealed that the interactions of the major compounds of the plant with AChE, BChE, GST, and alpha-Gly enzymes are responsible for the inhibitory activity.
Keywords: Antioxidant; Enzyme inhibition; Phenolic compounds; Thymus migricus; Docking